OTIMIZAÇÃO DO PROCESSO DE PRODUÇÃO DE BIODIESEL METÍLICO E ETÍLICO DO ÓLEO DE MAMONA (Ricinus Communis L.) APLICANDO UM DELINEAMENTO COMPOSTO CENTRAL ROTACIONAL (DCCR) - Brandão, Kiany Sirley Ribeiro (2007)
The biodiesel is a biofuel obtained from renewable sources, as vegetable oils and animal fats. The castor seeds (Ricinus communis L.) have a medium content of oil of 47%. This oil when transformed in biodiesel produces a fuel with a series of environmental advantages in relation to petroleum diesel. Therefore in this work it was made the optimization of the production process of the methyl and ethyl biodiesel from castor oil, varying the reaction time, the catalyst amount and the oil:alcohol ratio (methanol or ethanol) using a Central Rotatable Composite Design (CRCD) symmetrical and of second order, constituted of two parts: the factorial 2n, with central points, and the axial part. With base in this factorial planning, surfaces and curves of responses and variance analysis, it was evaluated the effects and the significance of the models for the responses variables, biodiesel yield in mass and the esters content. For the production of methyl biodiesel, the greater biodiesel yield in mass is reached when oil/methanol molar ratio 1:4-1:5; 0,4-1,2% of KOH and time reaction 20-100 min, is used. In function of the esters content, the oil/methanol molar ratio should be between 1:10 and 1:11,36, KOH concentration between 1,4 and 2,34 and reaction time between 120 and 140 min. The regression models of the methyl biodiesel for ANOVA appropriately explained at the level of 95%, the data variation (R2 = 0,90567, for yield biodiesel and R2 = 0,7654, for the esters content). For the production of the ethyl biodiesel, the results of the factorial planning 23 showed that the oil/ethanol ratio and the KOH concentration went statisticaly significant to the biodiesel yield in mass and content of esters. The maximum yield can be reached when oil/ethanol molar ratio between 1:10,4 and 1:12,35; 1,4 to 2% of KOH and 60- 100 min of reaction, is used. In function of the esters content, the oil/ethanol molar ratio should be between 1:10,5 and 1:12,35, concentration of KOH between 1,4 and 2,0 % and time of reaction between 60 and 120 min. The regression models explained the variation of the data appropriately (R2 = 0,71811, for biodiesel yield and for esters content, R2 = 0,95217) and they acted significantly, to 95% of trust limit, the relationship between the independent variables and the response. The samples of the methyl and ethyl biodiesel of castor oil, in the optimized conditions, they are inside of the limits preset by National Agency of the Petroleum, Natural Gas and Biofuels.